House price rises and borrowing to invest - Thomas Crossley; Peter Levell; Hamish Low (Institute for Fiscal Studies (IFS), 2020)
Household borrowing and spending rise with house prices, particularly for leveraged households, but household spending is not consumption. We propose an alternative borrow-to-invest channel by which house price gains affect household spending on residential investment. We show that rational, leveraged households have an incentive to make additional residential investments when house prices rise. Our empirical compares responses in different kinds of spending across more and less leveraged households. We find strong evidence of the borrow-to-invest channel in UK data. Credit constraints matter through reducing access to leveraged returns and so reducing lifetime resources, rather than through consumption smoothing.
Keywords: E21; D14; D15; G51; 330; House prices; leverage; consumption; home investment